Kritik Makna Islam Perspektif Orientalis dan Liberal - Syamsi Wal Qamar (Universitas Darussalam Gontor, 2015)
Islam is a name religion with clear explanation based on the arguments that are normative and historically, the Qur’an, Hadith and history of preaching Prophet Muhammad when spread this religion. Of course this naming is permanent so it will not be changed until the end of time later. But for Wilfreid Cantwell Smith and Muhammad Shahrur which are the thinkers of the West and the Muslim Orientalist Liberals are trying to recontruction naming them. For Smith, Islam is only submission to God to be obedient and submissive to the shari’ah religion are shared by humans, as judging that the word Islam is derived from the word aslama means surrender or submission. Meanwhile, according Shahrur, Islam is taught by the shari’ah of the Prophet Muhammad who was also taught by the previous Prophets such as Abraham, Moses, Jesus and others. So according Shahrur Muslim person can be said without having to follow and believe in the Shari’ah as taught by the Prophet Muhammad. From this a second thought leaders cause various problems, such as Islamic religious truth is relative or inclusive or decontructed concept and the Shari’ah of Islam. So in this paper the authors will describe how Smith and Shahrur view of the meaning of Islam, the background of their thinking and their implications for the Islamic religion, and a refutation of their thinking.